UNIX system administration handbook - Nemeth, Evi (Prentice Hall PTR, 2001)
Suitable for courses in UNIX-Intro/Advanced and System Administration, this guide to Unix system administration combines theory with practical application to explore Solaris, HP-UX, Free BSD, and significant coverage of Linux.